A Model For Creating Business Competitiveness Based On Technosociopreneur Innovation Characterized By State Defense Values - Sari, Rida Perwita; Sulistyowati, Erna; Sari, Rika Puspita (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: This research aims to find a model for creating business competitiveness based on technosociopreneur innovation characterized by state defense values in the new normal era for MSMEs in Surabaya so that they can survive and be sustainable in the new normal era. The challenge of MSMEs in the new normal era is the increase in unemployment and poverty, as well as the global economic downturn, becoming a momentum for adaptation in maintaining business sustainability. MSMEs that succeed in shifting both behavior and economic activity will be able to win. The new normal changes entrepreneurial motives not only profit oriented but also social oriented by using digital technology or known as Technosociopreneur.Methodology: This research uses a mixed method approach which is an approach in research that combines or connects qualitative and quantitative research methods (including philosophical foundations, using approaches and combining both approaches in research).Finding: Technosociopreneurs have a significant role in dealing with technological changes and increasingly fierce business competition. They can combine technological and social elements to create innovations that positively affect business and society. The success of technosociopreneurs can positively impact achieving higher competitiveness in today's digital era.Conclusion IT-based product innovation affects competitiveness mediated by technosociopreneur IT-based process innovation has an effect on competitiveness mediated by technosociopreneur. IT-based organizational innovation affects competitiveness mediated by technosociopreneur 7.